2023
DOI: 10.3389/fmicb.2023.1146065
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol potential of wine yeasts against four grape phytopathogenic fungi disclosed by time-course monitoring of inhibitory activities

Abstract: Grapes’ infection by phytopathogenic fungi may often lead to rot and impair the quality and safety of the final product. Due to the concerns associated with the extensive use of chemicals to control these fungi, including their toxicity for environment and human health, bio-based products are being highly preferred, as eco-friendlier and safer alternatives. Specifically, yeasts have shown to possess antagonistic activity against fungi, being promising for the formulation of new biocontrol products.In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…[31]. Moreover, their natural environment is the optimal source of antagonistic yeast strains, and they have already shown the aptitude to successfully outcompete other microorganisms [32]. Therefore, the selection of native non-Saccharomyces wine grape yeasts as BCAs against the major fungal pathogens of wine grapes as well as the use of commercial non-Saccharomyces yeast-based BCAs in vineyards have been addressed by numerous researchers.…”
Section: Biocontrol In Wine Grapesmentioning
confidence: 99%
See 2 more Smart Citations
“…[31]. Moreover, their natural environment is the optimal source of antagonistic yeast strains, and they have already shown the aptitude to successfully outcompete other microorganisms [32]. Therefore, the selection of native non-Saccharomyces wine grape yeasts as BCAs against the major fungal pathogens of wine grapes as well as the use of commercial non-Saccharomyces yeast-based BCAs in vineyards have been addressed by numerous researchers.…”
Section: Biocontrol In Wine Grapesmentioning
confidence: 99%
“…Additionally, intraspecific variabilities were noticed among some of the tested species (W. anomalus, Candida oleophila and Zygoascus meyerae). A recent work carried out with 397 wine yeasts belonging to 32 species isolated from Portuguese wine regions found only 3 strains (H. uvarum, L. thermotolerans, and S. bacillaris) displaying strong or very strong inhibition against the most common grape phytopathogenic fungal genera tested (Aspergillus, Botrytis, Mucor, and Penicillium) [32]. Although more studies are needed to obtain a conclusion, it seems that broad-spectrum antifungal activity is not a common feature among viticultural yeasts and raises the question as to whether a single microorganism-based biofungicide could provide sufficient protection against numerous different pathogens.…”
Section: Improvements In Non-saccharomyces Bcas Applied To Wine Grapesmentioning
confidence: 99%
See 1 more Smart Citation
“…As concerns about environmental pollution and food safety rise, many traditional vineyards are transitioning to organic practices. In this context, research has shown that grape surfaces harbor numerous microorganisms that can be harnessed for local antagonism, providing an environmentally friendly alternative to pesticides and mitigating food safety concerns arising from pesticide residues [4][5].…”
Section: Introductionmentioning
confidence: 99%